ANALYSIS OF A WORK OF ART THROUGH THE PRISM OF PHILOLOGY AND A CONCEPTUAL APPROACH (Web of Teachers: Inderscience Research, 2025)
This paper examines the latest achievements of modern linguistics, among which the theory of concepts stands out. It is based on the application of the method of phenomenological reductions, which allows us to trace the movement from specific material objects to abstract ideal entities, from the external manifestation (phenomenon) of a concept to its internal nature (concept). The use of philological and conceptual approaches in the analysis of works by Russian writers and poets, taking into account the features of concepts and their mental characteristics, allows for a deeper understanding of the author's perception of national character, connections with the spiritual heritage of the people, and also provides researchers with a more objective view of such categories as “people’s writer (poet)” and “people’s character in literature and art”.